Hell hath no fury [videorecording (DVD)] - McEwan, Katharine; Bergman, Nina; Bernhardt, Daniel; Mandylor, Louis; Murphy, Timothy V. (Well Go USA, 2021)
Branded a traitor by her countrymen, French national Marie DuJardin is rescued by American soldiers on one condition: to survive, she must lead them to a cache of gold hunted by the Nazis, the French resistance, and the Americans alike.